(untitled) (Al-Farooq Journal of Sciences, 2026)
This study investigates the impact of teaching English Literature as a one-semester elective course on the linguistic, cognitive, and affective development of fourth-year ESL students at Omar Al-Mukhtar University, Libya. Although these students have typically received years of formal English instruction, many still struggle to move beyond limited functional competence toward more advanced academic language use, critical reading, and analytical writing. To address this issue, the study employed a convergent parallel mixed-methods design with a quasi-experimental approach. Seventy fourth-year students participated in the study and were divided into an experimental group (n = 35), which studied English Literature, and a control group (n = 35), which followed a conventional advanced grammar and composition course over a 15-week semester. Data were collected through reading comprehension tests, writing assessment, the Watson–Glaser Critical Thinking Appraisal, Likert-scale attitudinal measures, and students’ reflective journals. The findings revealed statistically significant improvements in the experimental group across reading comprehension, writing quality, critical thinking, vocabulary retention, and learner motivation. The currently available descriptive results show higher post-test performance for the literature group in reading comprehension (78% vs. 69%), writing quality (4.4 vs. 3.8), and critical thinking (26 vs. 19), alongside positive shifts in learner motivation. Qualitative data further indicated enhanced confidence, stronger engagement with English, and greater cultural and interpretive awareness. At the same time, challenges related to cognitive load, text difficulty, and limited instructional time were observed. The study concludes that literature should be viewed not as an optional enrichment component, but as a pedagogically valuable intervention that can support advanced language development in university ESL contexts.